Preoperative Sarcopenia in Predicting Postoperative Complications following Gastrointestinal Cancer Surgery: An Observational Study - Narendra Maharjan; Paleswan Joshi Lakhey; Sumita Pradhan; Bishnu Prasad Kandel; Ramesh Singh Bhandari (Journal of Nepal Medical Association)
Introduction: Surgery is the mainstay for the management of gastrointestinal cancer patients, but it is associated with various complications. So, identification of pre-operative factors associated with post-operative complications is essential. Sarcopenia is increasingly recognized as a prognostic factor of post-operative complications following various cancer surgeries. This study aimed to determine whether preoperative sarcopenia is associated with postoperative complications following gastrointestinal cancer surgery.